2017
DOI: 10.18632/oncotarget.16840
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenesis and gene aberration-related therapy may improve overall survival in patients with concurrent KRAS and TP53 hotspot mutant cancer

Abstract: PurposeGenetic alterations such as activating KRAS and/or inactivating TP53 are thought to be the most common drivers to tumorigenesis. Therefore, we assessed phase I cancer patients with KRAS+/TP53+ mutations.ResultsApproximately 8% of patients referred to phase I clinical trials harbored concurrent KRAS and TP53 mutations. Patients who received a phase I trial therapy (n = 57) had a median OS of 12 months, compared with 4.6 months in those who were not treated (n = 106; p = 0.003). KRAS G13 and TP53 R273 mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…Additionally, patients with KRAS hotspot mutations at locations other than codon G12 had significantly worse OS than did patients with KRAS hotspot mutations at codon G12 and KRAS - patients. This finding is consistent with our and others’ previous findings that patients harboring mutations at codon G13 had significantly worse OS than did those without mutations at this codon [ 28 , 35 , 36 ]. This finding may enhance future drug development targeting KRAS mutations to differentiate subgroups of KRAS -mutant NSCLC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, patients with KRAS hotspot mutations at locations other than codon G12 had significantly worse OS than did patients with KRAS hotspot mutations at codon G12 and KRAS - patients. This finding is consistent with our and others’ previous findings that patients harboring mutations at codon G13 had significantly worse OS than did those without mutations at this codon [ 28 , 35 , 36 ]. This finding may enhance future drug development targeting KRAS mutations to differentiate subgroups of KRAS -mutant NSCLC.…”
Section: Discussionsupporting
confidence: 93%
“…We previously reported on an outcome analysis of patients with metastatic KRAS and TP53 hotspot-mutant solid tumors in a phase 1 trial center [ 28 ]. In the present study, we focused on the impact of KRAS and/or TP53 hotspot mutations on patients with metastatic NSCLC as well as the impact of phase 1 clinical trial therapy on their survival.…”
Section: Discussionmentioning
confidence: 99%
“…16 Additional studies have demonstrated statistically significant improvements in clinical outcomes (such as response rate, progression-free survival, and overall survival) among TP53-mutant patients treated with anti-VEGF or anti-VEGFR therapies, compared to TP53-wild-type populations. [17][18][19][20] The increased expression of VEGFA may explain the improved response to VEGF/ VEGFR inhibitors in TP53-mutant populations, but to date, datasets have only interrogated a relatively small number of patients. Herein, we present an analysis of TP53 mutation status and VEGF/VEGFR expression in a large pan-cancer cohort, using a collection of 7525 tumor samples from The Cancer Genome Atlas (TCGA).…”
Section: Introductionmentioning
confidence: 99%
“…Archival formalin-fixed, paraffin-embedded tissue blocks, core biopsy specimens, or surgical resection specimens were used for TP53 mutation assessment. TP53 mutation assessment was performed in a Clinical Laboratory Improvement Amendment−certified molecular diagnostic laboratory at MD Anderson Cancer Center (for hotspots 2 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] , as well as at Foundation Medicine (for the entire coding sequence), as described previously [47][48][49] .…”
Section: Evaluation Of Toxicity and Efficacymentioning
confidence: 99%
“…In cancer cells, TP53 mutations are associated with elevated HIF-1α levels, which augment the HIF-1α−dependent transcriptional activation of the VEGF gene in response to tumor hypoxia 15 , and mediate resistance to cancer therapy 16 . In addition, we found that among cancer patients receiving VEGF inhibition− based therapies, the progression-free survival (PFS) durations of patients with mutated TP53 were significantly longer than those of patients with wild-type TP53 [16][17][18][19] .…”
mentioning
confidence: 99%